2006
DOI: 10.1007/s00542-006-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

Micro-machining processes for microsystem technology

Abstract: By means of experiments it could determined that micro-machining processes as grinding, drilling and milling are a good addition to the established production technologies in micro technology. To machine hard and brittle materials grinding with diamond tools is well suitable, but the kinematics of the grinding process, as well as the process strategy has a significant influence on the machined surface quality and the chipping of the edges. The study of micro-machining processes showed, that micro cutting proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…In an attempt to fill the niche between macro-scale machine tools and the micro world, a novel five-axis micro milling machine has been developed for fabrication of micro-scale components (Bong-Bang et al, 2005). It has also been shown that scaling-down of machine-tool processes must consider kinematic effects that can potentially occur when a tool, such as a micro-grinder or micro-drill, contacts a micro-scale material component during the fabrication process (Denkena et al, 2006). These effects can impart undesired surface movement, which translates into a reduction of the machine resolution and overall quality of the machined surface.…”
Section: Micro Milling Machinesmentioning
confidence: 97%
“…In an attempt to fill the niche between macro-scale machine tools and the micro world, a novel five-axis micro milling machine has been developed for fabrication of micro-scale components (Bong-Bang et al, 2005). It has also been shown that scaling-down of machine-tool processes must consider kinematic effects that can potentially occur when a tool, such as a micro-grinder or micro-drill, contacts a micro-scale material component during the fabrication process (Denkena et al, 2006). These effects can impart undesired surface movement, which translates into a reduction of the machine resolution and overall quality of the machined surface.…”
Section: Micro Milling Machinesmentioning
confidence: 97%
“…Micro milling is proved to be a very cost effective machining technology for the micro structuring of lPIM mould inserts made not only from unalloyed steels but also from tool steels with a hardness of more than 700 HV (Denkena et al 2006;Fleischer et al 2005;Schmidt and Kotschenreuther 2005). Depending on the diameter of the milling tool smallest details in the range of a few 10 lm were successfully produced.…”
Section: Introductionmentioning
confidence: 98%
“…Today the most common processes for the production of micro mould inserts made from steel are micro milling, electrical discharge machining (EDM) and laser ablation (Denkena et al 2006;Fleischer et al 2005;Fleischer and Kotschenreuther 2007;Schmidt and Kotschenreuther 2005;Schulze et al 2010). Very often the obtainable surface quality isn't adequate for lPIM, because of burrs and grooves resulting from micro milling or rough and brittle recast layers resulting from EDM or laser ablation processes (Horsch et al 2005;Cusanelli et al 2004;Le Harzic et al 2005).…”
Section: Introductionmentioning
confidence: 98%